Non syndromic primary diffuse leptomeningeal melanomatosis in a child: a case report - Tavana Rad, Salim; Ashrafzadeh, Farah; Golmakani, Hassan; Ganjeifar, Babak (Iranian Journal of Child Neurology, 2021)
Abstract In this study, a case of primary diffuse leptomeningeal melanomatosis (PDLM), without neurocutaneous melanosis syndrome, is presented. A female patient (age, 14 years) presented with headache, nausea, vomiting, vertigo, diplopia, and lower limb weakness. Definitive histological examination showed a densely cellular tumor, characterized by irregular clusters of large pleomorphic cells and melanin in tumor cells. Adjuvant therapy was refused by the parents, and the patient died within 6 months. PDLM is recognized as an uncommon and malignant melanoma affecting the central nervous system. In case comorbidities are not diagnosed in patients with unusual symptoms of meningitis, diagnostic methods such as cerebrospinal fluid analysis and CNS biopsy can be helpful in identifying other underlying conditions.